Produção de éteres de glicerina com aquecimento por microondas - Cavalcante, Kiany Sirley Brandão (2011)
Due to the large production of crude glycerin by the Brazilian biodiesel industries, nowadays the commercial interest for glycerol derivatives has widely increased. Several methodologies for obtaining fuel additives from glycerin have been proposed, but require a very long reaction time. In this context, they were prepared niobia catalytic and tested in babassu oil transesterification and glycerin etherification. It was made the investigated the influence of microwaves in the glycerin tert-butylation reaction to production of glycerol ethers, potential additive for diesel oil. The reactions of tert-butilation were evaluated by acid catalysis homogeneous and heterogeneous, and without catalyst. It was applied in the optimization of chemometric techniques in glycerin tert-butilation, catalyzed with sulfuric acid and microwave heating, based on the percentage of conversion of glycerin quantified by a chromatographic method. Finally, we analyzed the diesel oil (B5) added with the glycerol ethers according to some physical-chemical parameters and gas emissions. Microwave heating applied in the reactions of glycerin tertbutilation to formation of glycerol ethers in short reaction time compared with the reaction using heating by thermal conduction, and the variables that most influence the process: catalyst and reaction time. The niobia catalysts did not show good catalytic activity in glycerin tert-butilation with microwave heating, due to the absence of agitation the reaction system, but implementation of niobia anchored on alumina, provided a babassu oil transesterification and heating by thermal conduction, with a income of more than 90%. The chromatographic method developed showed an excellent separation and resolution of the compounds under study, and a good linearity, precision and accuracy. The mixture B5/GTBE made some changes in its physico-chemical and pollutant emissions, confirming its potential for such particular purpose.